Current disclosure practices by Zakat Institutions in Malaysia: An exploratory study - Sapingi, Raedah; Puat Nelson, Sherliza (2016)
To fulfill the concept of maqasid shari’ah as well as to be in lined with the efforts from the Malaysian National Audit Department (MNAD) in improving accountability and transparency in the public sectors, zakat institutions are no exceptions in this case. Zakat institutions need to ensure that the funds collected and disbursed are reported accordingly. Prior studies have shown that zakat payers’ were dissatisfied on the lack of information disclosed in zakat disbursement’s information among zakat institutions in Malaysia. Hence, leads to questions of accountability in the dissemination of information that might have caused from the inconsistencies in the disclosure practices among zakat institutions in Malaysia. Further, the nonexistence of a regulatory body or, zakat accounting standards to regulate and provide guidelines for reporting and disclosure, increases the information gap. Therefore, this study intends to investigate the current disclosure practices among zakat institutions; that put focus on financial, nonfinancial and governance information. Semi-structured interviews were conducted with zakat payers. The findings highlight that zakat payers were of the opinion that disclosures practices among zakat institutions were inadequate. The study concludes that the issue of accountability among zakat institutions is still questionable and many rooms need to be improved